EVALUASI PROGRAM PENYULUHAN USAHA PETERNAKAN SAPI DI KECAMATAN SINONSAYANG KABUPATEN MINAHASA SELATAN - Sajow, Nissa; Sondakh, B. F.J.; Legrans, R. A.J.; Lainawa, J. (Universitas Sam Ratulangi, 2014)
ABSTRACT EXTENSION PROGRAM EVALUATION IN CATTLE FARM BUSINESS AROUND INONSAYANG DISTRICT, SOUTH MINAHASA REGENCY. Sinonsayang district is located in the regency of South Minahasa consisted of 13 villages and area size of 12,960 ha. Generally, Sinonsayang communities were living as farmers / ranchers. The highest populations of cattle were focused in 3 villages around Sinonsayang district including Blongko Village, Ongkaw II and III Villages (296 cattle). The problem of this study was how far the success of extension program in terms of improving education of BP3K for cattle population in the district of Sinonsayang, South Minahasa Regency. The objective of this study was to evaluate the implementation of extension activities around Sinonsayang district, South Minahasa regency. The research was conducted in January to February, 2014 using survey method at the 3 sampling villages with the highest cattle population. The respondents were farmers and ranchers who were randomly targeted for outreach assigned to 30 people (respondents). Research and data collection were done during 2 months. The data in this study were obtained from two sources (primary data and secondary data). Method of purposive sampling was done intentionally. The use of this technique was based on certain characteristics obtained through the population. The results in this study indicated that the extension was not successfully and effectively done by BP3K, because the extension service can only reach few numbers of breeders. Therefore more farmers had less motivation to breed their cattle population. Keywords: Evaluation, Extension, Livestock Cattle